Proposal to Improve Employability and Facilitate Entrepreneurship among Graduates of the Master’s Degree in Institutional Translation of the University of Alicante - Cuadrado-Rey, Analía; Navarro-Brotons, Lucía (HERMES - Journal of Language and Communication in Business, 2020)
The aim of this article is to describe the strategies included in our proposal to improve employability and facilitate entrepreneurship among graduates of the Master’s Degree in Institutional Translation. Firstly, this paper takes as a starting point the survey data collected by the Technical Unit for Quality Assessment (UTC) at the University of Alicante. This data shows the evaluation done by the graduates of the Master’s Degree in Institutional Translation on the competences preparing them for graduate labour market outcomes and entrepreneurship. Secondly, it explains the different curricular and extracurricular activities, as well as elective subjects, which are either being carried out at the moment or to be implemented in the future, so that students can develop the competences that the translator’s profession requires. The paper also mentions the role played by each institutional party involved in this collaborative action and proposes measures to consolidate and further develop the initiative.